Methods of identifying elements for inter-organizational knowledge sharing - Ahmad Shukor, Nur Syufiza (Universiti Teknologi Malaysia, 2013)
In the knowledge management field, knowledge sharing is considered as a very important activity in order for the organization to make decision related to their day-t-day and complicated tasks. Working with different organizations that have different beliefs, culture and work flow will make the knowledge sharing more complex. Thus identifying the influencing factors for the organizations to share their knowledge is important. This paper shows how data based on the interview done from 19 respondents is analyzed. Interviews were carried out among the departments that involved in the flood management. The Straussian approach was used in analyzing the qualitative data. The results shows the emerging themes were identified while coding the data being technology, organizational, political and policy and coordination.